Mycoplasma gallisepticum Infection Impaired the Structural Integrity and Immune Function of Bursa of Fabricius in Chicken: Implication of Oxidative Stress and Apoptosis - Zhang, Wei; Liu, Yuhao; Zhang, Qiaomei; Waqas Ali Shah, Syed; Wu, Zhiyong; Wang, Jian; Ishfaq, Muhammad; Li, Jichang (Frontiers in Veterinary Science, 2020)
Mycoplasma gallisepticum (MG) induces a dysregulated immune response in the lungs and air ways of poultry. However, the mechanism of MG-induced immune dysregulation is still not completely understood. In the present study, the effect of MG-infection on chicken bursa of fabricius (BOF) is investigated. Histopathology, electron microscopy, TUNEL assay, qRT-PCR and western blot were employed to examine the hallmarks of oxidative stress and apoptosis. The data revealed that MG-infection induced oxidative stress and decreased antioxidant responses in BOF tissues compared to control group. Histopathological study showed pathological changes including reduction in lymphocytes and increased inflammatory cell infiltration in MG-infection group. Ultrastructural assessment represents obvious signs of apoptosis such as mitochondrial swelling, shrinkage of nuclear membrane and fragmentation of nucleus. Increased cytokine activities were observed in MG-infection group compared to control group. Meanwhile, the mRNA and protein expression level of apoptosis-related genes were significantly (p < 0.05) upregulated in MG-infection group. Terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) assay further confirmed that MG induced apoptosis in BOF tissues as TUNEL-stained positive nuclei were remarkably increased in MG-infection group. In addition, MG-infection significantly reduced the number of CD8+ lymphocytes in chicken BOF at day 7. Moreover, bacterial load significantly increased at day 3 and day 7 in MG-infection group compared to control group. These results suggested that MG-infection impaired the structural integrity, induced oxidative stress and apoptosis in chicken BOF tissues, which could be the possible causes of damage to immune function in chicken BOF.